2016
DOI: 10.14434/ijdl.v7i3.19520
|View full text |Cite
|
Sign up to set email alerts
|

From 2D to Kubi to Doubles: Designs for Student Telepresence in Synchronous Hybrid Classrooms

Abstract: This paper introduces the efforts of Michigan State University's Counseling, Educational Psychology, and Special Education/College of Education (CEPSE/COE) Design Studio to utilize robotic telepresence devices in synchronous hybrid learning classes for the Educational Psychology and Educational Technology (EPET) Ph.D. program. Robotic telepresence devices are digital devices that can be piloted from a distance for the purpose of interacting with people in a remote location. Synchronous hybrid learning classes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…One challenge is that social presence-an important aspect of a successful learning experience (Chickering & Gamson, 1987)-is often more difficult for online students to form. Online students, especially, often complain about feeling disconnected from their instructor in the learning environment (Smith & Taveras, 2005) or as interrupting interactions happening in the physical space of the classroom (Bell, Cain, Peterson, & Cheng, 2016). Establishing social presence, or the ability of students to project their personal characteristics into the community of inquiry, thereby presenting themselves to other participants as "real people" (Garrison, Anderson, & Archer, 2000, pp.…”
Section: Review Of Related Literaturementioning
confidence: 99%
“…One challenge is that social presence-an important aspect of a successful learning experience (Chickering & Gamson, 1987)-is often more difficult for online students to form. Online students, especially, often complain about feeling disconnected from their instructor in the learning environment (Smith & Taveras, 2005) or as interrupting interactions happening in the physical space of the classroom (Bell, Cain, Peterson, & Cheng, 2016). Establishing social presence, or the ability of students to project their personal characteristics into the community of inquiry, thereby presenting themselves to other participants as "real people" (Garrison, Anderson, & Archer, 2000, pp.…”
Section: Review Of Related Literaturementioning
confidence: 99%
“…J. Bell [9] studied the incarnation of distant students in hybrid teaching, from videoconferencing to the use of the telepresence robots. It appears robot getting closer to a feeling of physical presence.…”
Section: Use Of Rpr In Different Departments Remote Presence Robots I...mentioning
confidence: 99%
“…Subsequent research demonstrated that telepresence robots can minimize the effects of physical separation during school absences of K-12 students [37]. Multiple studies have also shown ways for telepresence robots to provide better experiences than other distance learning technologies, albeit in university classrooms [2,17,19].…”
Section: Introductionmentioning
confidence: 99%